PEDAGOGICAL AND PSYCHOLOGICAL BASIS OF DEVELOPMENT OF KNOWLEDGE OF UZBEK MUSIC HISTORY IN FUTURE MUSIC EDUCATION TEACHERS (Scientific journal of the Fergana State University, 2024)
In this article, the issues related to the process of researching the socio-pedagogical necessity of improving the educational process for the development of the axiological attitude of students to the national musical heritage of future music education teachers are scientifically analyzed.